The genus Euryparasitus in North America (Mesostigmata: Euryparasitidae) - Hagele, Thomas; Kaufman, Bruce; Whitaker, John O.; Klompen, Hans (Zootaxa, 2005)
The genus Euryparasitus in North America is revised on the basis of the deutonymphal instar. Four species are recognized, two previously described and two new. The four species fall into two easily recognizable groups. The first group, consisting of E. longicheta Bondartchuk & Buyakova and E. occidentalis n. sp., lacks barbed setae on the idiosoma and serrations on the anterior free margin of the gnathotectum, and shows a well differentiated acrotarsus on legs I. The second, consisting of E. calcarator (Banks) and E. maseri n. sp., has barbed setae on the idiosoma and serrations on the anterior margin of the gnathotectum, but lacks a well differentiated acrotarsus I. A key to the deutonymphs for the species of Euryparasitus and genera of Euryparasitidae in North America is provided. The host association pattern of Euryparasitus species appears to fit better with ecological than with host specificity.